Education And Implementation Of Hypertension Exercise As An Effort To Control Hypertension Among The Elderly In Rt 05, Senalang Village, Lubuklinggau City - Dini Aprilia; Yuan Apriyanti; Deni Novriyanto; Indri Yusmeli; Leni Abriyanti; Murwati Murwati (Jurnal Pengabdian Mandiri, 2026)
Hypertension is one of the major health problems among the elderly and can increase the risk of cardiovascular disease, stroke, and kidney failure. Efforts to control hypertension are not only carried out pharmacologically but also through non-pharmacological approaches such as physical activity. Hypertension exercise is a form of light physical exercise that is safe and effective for the elderly. This Community Service Program (KKN) aimed to determine the effect of education and implementation of hypertension exercise on the knowledge level of the elderly as an effort to control hypertension in RT 05, Senalang Village, Lubuklinggau City. The method used was health education with a pre-test and post-test design involving 39 elderly participants and community health cadres. The results showed an increase in participants’ knowledge levels after education and demonstration of hypertension exercise. Before the intervention, most participants had a moderate level of knowledge (80%), while after the intervention, the majority had a good level of knowledge (80%). Education and implementation of hypertension exercise proved to be effective in increasing awareness and knowledge of the elderly to independently control hypertension.